Epitaxial and large area Sb2Te3 thin films on silicon by MOCVD. Issue 34 (27th May 2020) - Rimoldi, Martino; Cecchini, Raimondo; Wiemer, Claudia; Lamperti, Alessio; Longo, Emanuele; Nasi, Lucia; Lazzarini, Laura; Mantovan, Roberto; Longo, Massimo
Abstract : Highly oriented antimony telluride thin films are prepared by room temperature metalorganic chemical vapor deposition on Si(111). Abstract : Antimony telluride (Sb2 Te3 ) thin films were prepared by a room temperature Metal–Organic Chemical Vapor Deposition (MOCVD) process using antimony chloride (SbCl3 ) and bis(trimethylsilyl)telluride (Te(SiMe3 )2 ) as precursors. Pre-growth and post-growth treatments were found to be pivotal in favoring out-of-plane and in-plane alignment of the crystallites composing the films. A comprehensive suite of characterization techniques were used to evaluate their composition, surface roughness, as well as to assess their morphology, crystallinity, and structural features, revealing that a quick post-growth annealing triggers the formation of epitaxial-quality Sb2 Te3 films on Si(111).